The Impact of Ambiet Factors on Consumer Purchase Decisions (KKV Offline Store): Business - Azila, Nur Azila; Afif Zaerofi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The rise of globalization and the increasing dominance of information technology have ‎transformed the paradigm for business success. Infrastructure is no longer the sole foundation for ‎entrepreneurs. Instead, the economic landscape now places greater emphasis on intangible assets ‎such as intellectual capital. This includes elements like market perception, interpersonal ‎relationships, company ethos, brand reputation, patents, trustworthiness, strategic vision, and ‎specialized expertise. In this evolving economic environment, these intangible factors play a ‎pivotal role in determining the competitiveness and prosperity of businesses. This research uses ‎quantitative research methods and approaches. Data is collected through random sample ‎distribution of questionnaires to respondents. The respondents of this study are offline store ‎KKV visitors. In this study, ambient temperature are predictors that have significant correlations ‎and ‎influence, contributing to 43.8 percent of variance in customers purchase decisions.‎